It is about Islam : exposing the truth about Isis, Al Qaeda, Iran, and the Caliphate - Beck, Glenn (New York : Threshold Editions/Mercury Radio Arts, 2015)
From the barbarians of ISIS to the terror tactics of Al-Qaeda and its offshoots, to the impending threat of a nuclear Iran, those motivated by extreme fundamentalist Islamic faith have the power to endanger and kill millions. The conflict with them will not end until we face the truth about those who find their inspiration and justification in the religion itself.
Introduction: Jefferson's Quran -- Part one: Islam 101. Islam and the end times -- From revelation to empire -- Wahhabism and Salafism -- Reestablishing the Caliphate -- Part two: Thirteen deadly lies -- Lie #1: "Islam is a religion of peace, and Islamic terrorists aren't really Muslims." -- Lie #2: "Islam is not much different than Christianity or Judaism." -- Lie #3: "Jihad is a peaceful, internal struggle, not a war against infidels." -- Lie #4: "Muslims don't actually seek to live under sharia, let alone impose it on others; there are so many different interpretations of it anyway." -- Lie #5: "America is safe from sharia law." -- Lie #6: "The Caliphate is a fanciful dream." -- Lie #7: "Islam is tolerant toward non-Muslims." -- Lie #8: "Addressing frustration, poverty, and joblessness in the Muslim world - maybe even climate change - will end terrorism." -- Lie #9: "Critics of Islam are bigots." -- Lie #10: "Islam respects the rights of women." -- Lie #11: "Iran can be trusted with a nuclear women." -- Lie #12: "The Muslim Brotherhood is a moderate, mainstream Islamic group." -- Lie #13: "Islam respects freedom of speech." -- Part three: What can be done.
Subtitle from cover.
Includes bibliographical references (pages [231]-263).
Keywords: Qaida (Organization).; IS (Organization).; Islam; Islamic fundamentalism; Islam and politics -- Iran; Terrorism -- Religious aspects -- Islam